Labelling versus Understanding, News, Views, Opinions or Facts - Jeffrey W. Dance, Robert W. Service (Social Science Learning Education Journal, 2016)
The media in the United States are the âinfluentialsâ of the day. But, all too often their influence, purposeful or not, are agenda driven and based on incomplete and inaccurate âfacts.âThe current authorsâ experiences across the world say this is true in most other developed countries. Of course in some of the countries the press reports and government reports are the same, and in newly free or near free countries most do not trust their press. These assertionsare supported by antidotal evidence and careful analysis.Â  If you agree or not, read on to advance your thinking.By thinking to learn we learn to think.Â  We will provide insight into transferring understandable data into useful information.The key research question is: are we better off if the academy took a different approach to teaching, learning and publishing? Shallow understandings,witnessed and documented, during discussions and press reports of current events reinforce the âopinions based on little knowledgeâ phenomena that leads to the current quagmire of vastly opposing views. Readers of this current research and opinion manuscript are challengedto find scientific, medical and academically referred journal articles, and official governmental data before accepting the wisdom of the day or the pronouncements within this manuscript. In all we in the professoriate do keep in mind thatâThe work of the professor becomes consequential only as it is understood by others (Boyer, 2016: p. 13).â